FLYPAPER EFFECT PADA PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA DAERAH PEMERINTAH KOTA KUPANG PROVINSI NUSA TENGGARA TIMUR - Esteria Nivianny Zacharias; Rossy Lambelanova (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2018)
Central government financial transferred by balance allocation funds have function to decrease fiscal imbalance and produce equalization regional funds.  However, this policy in fact makes most of local governments, including Kupang City government, be depended on that funds especially General Allocation Funds, because of local government ability lack. These are some purposes of this research. First, this research purposes to know how far the locally generated income and general allocation funds give effect in significant to regional expenditure partially and simultaneously. Second, it purposes to know if there was a flypaper effect in Kupang City from 2008 to 2017. Finally, this research makes an analysis of basic principles to increase regional income in order to decrease dependency to central government. This result research shows locally generated income and general allocation funds have effect to regional expenditure of Kupang City in significant from 2008 to 2017. It is because the T statistic (T count) bigger than T chart, α = 1%. The locally generated funds is 2,617 and the general allocation funds 4,646. In simultaneous,  locally generated income and general allocation fund also give effect to regional expenditure significantly because of the F statistic bigger than F chart α = 1%. It is 154,061. This research also gets result that there was a flypaper effect, because the coefficient of general allocation fund bigger than locally generated income, it is 0,645 > 0,365. Flypaper effect happened to Kupang City government can be overcome by regional income increasing. The regional income increasing can be done by expansion of income base, income leakage control, and the increasing efficiency of tax administration.